The rhetorical appeal: Its grammatical provisions and its role in performing the meaning The seventh verse from Surat Al-Imran example - صالح أحمد أحمد إبراهيم; فضل خليل الشيخ (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research studies the rhetorical appeal in selected evidences from the Holy Qur’an - from Surat Al-Imran - identifies their positions and studies them descriptively and analytically. It also shows their relationship to the previous verses; whether in adjacent sentences or in distant sentences. The coherence appears in the textual structure of these noble verses, and the harmony of their meanings from a graphic point of view represented by the semantic control and the overall major structure of the discourse and the repetitive referral, away from the effect of the words and what comes after in the context which is the grammatical link between the sentences. The research presents a preface to a theoretical study that deals with the linguistic meanings of both the appeal and rhetoric. It also study the meaning of the rhetorical appeal idiomatically. In addition, it shows the differences between the grammatical appeal and the rhetorical appeal which is important because of its impact on clarifying the purpose for the research was written in showing the significance of the rhetorical appeal. It also a preface to the applied studying on the verses of surat AL-Imran to show the textual coherence between the verses of the surat and its topics. Finally, the research ends with the views of the researcher based on what the scholars of rhetoricians and interpreters said in this verse, and what God Almighty guided him to the opinions in the light of what is understood from the context of the verses.